GAMBARAN KEMANDIRIAN ANAK PLAY GROUP DALAM ELIMINASI URINE DI TK KEMALA BHAYANGKARI 05 WATUKOSEK KECAMATAN GEMPOL KABUPATEN PASURUAN - Hariyanto, Agus (JURNAL KEPERAWATAN SEHAT, 2015)
When the child enters play group, the child needs to introduce urine eliminations. Due to when the child is entered preschool, they will be loose from their parents to do anything such as including urine elimination. But this time, the children don’t have self government to do urine elimination. The puspose of this research measured self government image to urine elimination of children in play group. The metodh of this research was descriptive and the sample was children in play group who were aged 3-4 years old. They were choosen by inclution criteria, with total sampling is 15 respondents. For research survey was known self government image of children in play group got 9 respondents (60%) who were hanged easily for urine elimination by themselves. Many factors as sign or desire of the children who do expression to feel their urine elimination and learn toilet training less, because mother’s age is younger. So, their mother understand to give their children about toilet training. The mother’s job is a house wife and they are less disvantage their time in home for learn their children in deep toilet training before they reach urine elimination by themselves. Health educator and the others should give information to their family and the others who have children for learn about urine elimination. Whereas many mothers have much time for to do it, they can give toilet training for their children until their children have self government of urine elimination. So, the children can do it by themselves.Keyword: Self, Elimination urine, Child in Play Group